Non‐Pharmacological Interventions Before Cataract Surgery for Preoperative Anxiety: A Systematic Review and Meta‐Analysis - Mahsan Nabighadim; Mojgan Mirghafourvand; Mahsa Maghalian (Nursing Open)
ABSTRACT Aim The present study was conducted to determine the effect of non‐pharmacological interventions before cataract surgery on preoperative anxiety. Design Systematic review and meta‐analysis. Methods Five databases were systematically searched until 9 June, 2024. The risk of bias was evaluated using the ROBIN‐I instrument for non‐randomised studies and risk of bias 1 (ROB1) for RCTs. For cases with heterogeneity, random effects, rather than fixed effects, were reported, and subgroup analysis was performed based on the type of intervention. The investigation of publication bias was done in the form of a funnel plot, the Egger regression test and the Trim‐and‐Fill test. Meta‐regression analysis was performed to examine the impact of possible confounding factors on the effect size. Sensitivity analysis evaluated the robustness of our findings by excluding quasi‐experimental studies and applying the Knapp–Hartung method to assess their influence on the overall results. Results A random‐effects meta‐analysis of 22 studies and 1998 participants revealed that non‐pharmacological interventions (back massage, hand massage, foot massage, music, educational video, patient education, aromatherapy and relaxation techniques) significantly reduced mean preoperative anxiety compared to the control group. The subgroup analysis indicated that all interventions were effective in reducing preoperative anxiety; however, hand and foot massage did not yield significant effects. Meta‐regression analysis showed a significant correlation between the percentages of women with effect size. The sensitivity analysis confirmed the robustness of non‐pharmacological interventions, while the Knapp–Hartung method maintained the overall effect size but indicated wider confidence intervals. More high‐quality research is needed to validate these interventions and establish clearer guidelines. Patient or Public Contribution No Patient or Public Contribution.